ANALISIS YURIDIS PEMBUNUHAN JENDERAL SOLEIMANI DIKAITKAN DENGAN KONSEP TARGETED KILLING DALAM HUKUM HUMANITER INTERNASIONAL - Bintang Anugrah, Evelyn Zunita; Puspoayu, elisabeth Septin (Universitas Negeri Surabaya)
Abstract The United States under the direct direction of US President Donald Trump carried out targeted assassinations of General Qassem Soleimani, the head of Iran's elite Quds Force. Targeted killing is one of the uses of violence using the Targeted Killing method. The validity of targeted killing is only allowed on the basis of self defense after an armed attack. In fact, seen from the relationship between the two countries between Iran and the United States, no armed attacks were carried out by either side. The issues that will be discussed in this research are the validity of the targeted killing by the United States against General Soleimani according to international humanitarian law and the settlement of disputes against violations in the murder of General Solemaini. The purpose of this study is to analyze the validity of the targeted killing by the United States against General Soleimani according to international humanitarian law and to resolve disputes against violations of international humanitarian law regarding the targeted killings in the murder of General Solemaini. This research is a normative juridical study using a statute approach and a conceptual approach.